Implementasi kompetensi pembelajaran sepanjang hayat melalui program literasi di perpustakaan sekolah - Rahmat Fadhli (Jurnal Kajian Informasi dan Perpustakaan, 2021)
Lifelong learning can be developed through literacy programs in school libraries. This study aimed to determine the implementation of lifelong learning competence through literacy programs in school libraries. The research method used a qualitative approach through research methods a descriptive to a librarian, four teachers, and 22 students at Al Haraki Islamic Junior High School, Depok, West Java.  Through observation, data collection techniques were carried out using a lifelong learning dimension checklist form, semi-structured and in-depth interviews, and literature studies. Data analysis techniques were data reduction utilizing open coding, data presentation, and concluding. Study results indicated that the librarian organized literacy programs supporting the School Literacy Movement. In practice, the librarian acted as the initiator; the teacher became the facilitator and the librarian's partner in developing literacy programs in school. The literacy program had a positive impact on students, including shaping character, increasing knowledge, developing special talents related to communication and writing, adding experience, building positive relationships between librarians and students, and intellectual recreation. Communication competence in foreign languages was one of the lifelong learning competencies that the school library program did not accommodate. The literacy program's obstacles were managing study time and the roles of parents and family at home. This study concludes that the school library literacy program has supported improving the implementation of lifelong learning competencies for students in several dimensions.